Cypriot Archaelogy, Modern Numismatics and Social Engineering: The Iconography of the British Coinage of Cyprus - Hatzopoulos, Miltiades (The Historical Review/La Revue Historique, 2006)
This article examines the use of numismatic iconography by the British colonial administration of Cyprus in order, initially, to legitimise its possession of the island and, subsequently, to promote an Eteocypriot, an "authentic Cypriot", identity as counter-poison against Greek nationalism. In this endeavour of social engineering, archaeological items and other symbols from Cyprus' past played a prominent part. The outbreak of the Cypriot guerrilla war for union with Greece in 1955 highlighted the bankruptcy of this operation. Nevertheless, British efforts to evade Cyprus' overwhelmingly Greek past - and present - continued unabated, even after the formal recognition of the island's independence.